THE TUTORSHIP IN PROGRAMS OF DOCTORATE TUTORIAL TENSIONS AT THE DOCTORAL PROGRAM IN EDUCATIONAL SCIENCES OF RUDECOLOMBIA - Torres Calixto, Mario Gabriel (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2012)
The object of the work is to analyze the existing tensions in the development of the mentoring of the Doctoral Program in Educational Sciences of RUDECOLOMBIA, within the context of the international mentoring, with the question: ¿Do the tensions of the mentoring affect the quality of the work and integral formation of the doctoral student? The method focuses on the history of education that led to setting up the model to analyze the object of study as is the mentoring in a doctorate program. The qualitative methodology along with the comparative, provided us with the procedures, classification and organization of information that allowed us to understand the place that has occupied the mentoring in the training of doctors in RUDECOLOMBIA, from a review of national and international literature, they are contextualized within the concept of globalization and poses alternatives of solution. The strategies focused on the information about the workshops performed at the Curriculum Committee, in the 61 interviews carried out and the revision of the files of RUDECOLOMBIA. The results allowed us to identify that although there are rules on mentoring in the doctorate, there are still situations in which, the decision to take, depends on the autonomy of the mentor. This creates tensions, since there can be arguments in favor of or against such a decision, which affects the quality of the doctoral training. Conclusions: some recommendations are presented to implement the regulations and facilitate the decision-making in relation with the dilemmas and tensions that arise in the process of formation of the graduate; in addition, a proposal for training and/or permanent seminar of update for the mentor is presented.